2017
DOI: 10.3892/ijo.2017.3867
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FASN suppresses migration, invasion and growth in hepatoma carcinoma cells by deregulating the HIF-1α/IGFBP1 pathway

Abstract: Hepatocellular carcinoma is the second most common cause of cancer-related deaths worldwide. Due to a high propensity to metastasize, active angiogenesis and rapid proliferation, recurrence and poor prognosis are major obstacles for treatment and cure of this disease. However, the detailed mechanisms of how fatty acid synthase (FASN) promotes migration, invasion and healing in tumor cells remain unclear. In the present study, the previous results that FASN was expressed higher in cancer samples than in non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Gong et al reported inhibition of FASN can suppress migration, invasion, and healing of hepatoma carcinoma cells by decreasing HIF-1α and IGFBP1 (ref. 42 ). However, our results suggest that it may not be enough to inhibit the lipid synthesis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al reported inhibition of FASN can suppress migration, invasion, and healing of hepatoma carcinoma cells by decreasing HIF-1α and IGFBP1 (ref. 42 ). However, our results suggest that it may not be enough to inhibit the lipid synthesis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase (FASN), which catalyzes the final step in fatty acid synthesis, is often overexpressed in human cancers ( 93 , 94 ). Inhibition of FASN suppresses invasion and migration of HCC cells ( 95 ). In contrast to enhanced fatty acid synthesis, certain types of cancer rely on the mitochondrial fatty acid oxidation (FAO) for ATP production ( 96 ).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…We previously observed that ursolic acid, a natural pentacyclic triterpenoid, and emodin, one anthraquinones constituents derivative isolated from the roots of rheum palmatuma, inhibited growth of hepatocellular carcinoma and lung cancer cells through induction of IGFBP1 gene expression, suggesting tumor suppressing role of this molecule [31, 32]. However, conflicting results were observed in other cancer types, such as prostate [33, 34] and endometrial cancer [35] and others [36]. Thus, IGFBP1 may play dual roles depending upon the environmental content, cells examined, and agents exposed.…”
Section: Introductionmentioning
confidence: 99%